Interaction between inclusions and the TRIP effect during tensile loading of an L-PBF 18Ni-300 maraging steel and effect on ductility - T. Tekin; F. Naclerio; R. Ipek; A. Molinari (Journal of Materials Research and Technology)
The influence of non-metallic inclusions on the tensile ductility of a direct aged 18Ni300 maraging steel produced by L-BBF was investigated on two materials having the same microstructure and a different content of non-metallic inclusions. The strain-induced transformation of austenite promotes the TRIP effect enhancing ductility. In the presence of a high amount of inclusions, the minimum strain needed to trigger strain-induced transformation is reached after necking, and the transformation cannot contribute to ductility. The effect of inclusions is to promote stress rising and strain accumulation, but mostly to make TRIP uneffective. To recover the effectiveness of TRIP and, in turn, increase ductility, the stability of reverted austenite should be reduced, in order to anticipate its transformation in martensite that is able to extend the uniform deformation step.